2016
DOI: 10.1016/j.aquatox.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional changes in Crassostrea gigas oyster spat following a parental exposure to the herbicide diuron

Abstract: The Pacific oyster Crassostrea gigas is the main oyster species produced in the world, and a key coastal economic resource in France. High mortalities affect Pacific oysters since 2008 in France and Europe. Their origins have been attributed to a combination of biotic and abiotic factors, underlining the importance of environment quality. The impact of water pollution has been pointed out and one of the pollutants, the genotoxic herbicide diuron, occurs at high concentrations all along the French coasts. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 49 publications
(39 reference statements)
0
23
0
Order By: Relevance
“…We then selected the top ten high-and low-glycogen contents individuals to conduct transcriptome and metabolome analysis. However, because of the significant variation among individuals, we increased the sample number in the transcriptome analysis to fifteen, which clearly provided an increase in accuracy compared to previous studies in which no more than five biological replicates were used [ 18 , 22 ]. An integrative analysis of the transcriptome and metabolome allowed us to present a comprehensive overview between the genes and the metabolites controlling oyster glycogen content as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We then selected the top ten high-and low-glycogen contents individuals to conduct transcriptome and metabolome analysis. However, because of the significant variation among individuals, we increased the sample number in the transcriptome analysis to fifteen, which clearly provided an increase in accuracy compared to previous studies in which no more than five biological replicates were used [ 18 , 22 ]. An integrative analysis of the transcriptome and metabolome allowed us to present a comprehensive overview between the genes and the metabolites controlling oyster glycogen content as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, rapid advances in technology have made next-generation sequencing suitable to conduct large-scale searches to identify candidate genes related to different phenotypes [ 18 20 ]. However, a phenotype is not only regulated by genes but is also regulated at multiple other levels, including at the metabolite level.…”
Section: Introductionmentioning
confidence: 99%
“…However, strong transcriptional modulations of Hsps were observed in the diuron-exposed C . gigas (two 7-day exposure pulses to 0.2–0.3 μg L -1 diuron) [24]. These results suggest that up-regulated Hsp transcripts generated by the antifouling biocide treatments confer cell protection which enables oysters to survive from the detrimental damage.…”
Section: Discussionmentioning
confidence: 99%
“…In C . gigas , the effects of diuron have continuously been reported from molecular to physiological level such as genotoxicity, embryotoxicity, spematotoxicity and immunity [1824]. …”
Section: Introductionmentioning
confidence: 99%
“…By a transcriptional approach, we showed that exposure of oyster genitors to diuron at environmental concentrations affected gene expression including genes encoding enzymes involved in DNA methylation machinery [ 39 ]. In the offspring, a RNA-seq analysis demonstrated significant change in the transcriptional profile on F1 spat as well [ 40 ] that could explain developmental and growth impairment observed in F1 early life stages [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%